Inheritance and mapping of transgene in a transgenic ‘Golden Rice’ line of japonica rice (Oryza sativa) variety ‘Taipei 309’ - TYAGI, N K; RAMESH, B; MOHAPATRA, T; PRABHU, K V; SINGH, A K (The Indian Journal of Agricultural Sciences, 2010)
Transgene inheritance is an important consideration for the development of commercially viable transgenic crops. The F1, F2 and BC1F1 to BC3F2 populations of the cross ‘Taipei 309’ × ‘Swarna’ were used to analyze the inheritance of carotenogenic transgene(s) psy+crtI. Segregation distortion was observed for the transgene in F2 population. However, in BC1F1 and subsequent backcrosses and their selfed generations, the segregation of transgene positive and transgene negative plants occurred in an expected 1:1 and 3:1 ratio, respectively. In introgression breeding one can often encounter linkage drag due to linkage of some undesirable genetic loci to the gene under transfer thereby affecting the phenotype of the final converted lines. Therefore, mapping and identification of flanking molecular marker linked to the target gene is necessary for elimination of linkage drag. The F2 population from the ‘Taipei 309’ × ‘Swarna’ cross was used for tagging and mapping of the carotenogenic genes in transgenic ‘Taipei 309’ with 48 polymorphic STMS markers spanning over 12 rice chromosomes for Bulked Segregant Analysis (BSA). The transgene was mapped to the chromosome 4 in the vicinity of the markers RM252, RM3785 and RM7563 at a distance of 10.65 cM, 8.19 cM and 5.73 cM, respectively. The information generated will be useful in integrating transgenic lines into breeding programme